Extensive research of the consumer perspective on Pant/Pull up diapers. a thorough analysis of Square Toiletries Limited - Chowdhury, A S M Rafat Rahim (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.